2022
DOI: 10.7166/33-3-2784
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Holistic Diesel Management System to Reduce Wastage in Open-Cast Gold Mining

Abstract: Fuel prices in South Africa are variable and steadily rising. Diesel accounts for a large portion of operational expenditures in open-cast mining, placing pressure on fleet managers to address fuel theft and wastage. Raw data is often obtained in a variety of formats (handwritten or digital) in this environment. A need therefore exists to capture, interpret, and utilise raw diesel data to gain insights for decision-making. It is critical to develop a diesel management system that can monitor and track fuel usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…In a previous work [15], the application of DIKW was divided into two domains: the data domain and the analysis domain. This study follows the same principle but integrates Six Sigma's DMAIC tool, adding components that do not form part of DIKW, namely RCA, improvement, and control.…”
Section: Results and Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous work [15], the application of DIKW was divided into two domains: the data domain and the analysis domain. This study follows the same principle but integrates Six Sigma's DMAIC tool, adding components that do not form part of DIKW, namely RCA, improvement, and control.…”
Section: Results and Findingsmentioning
confidence: 99%
“…Several methodologies have been developed to manage diesel in open-cast mines due to their high diesel demand and increasing diesel prices. Previously [15], it was shown that the DIKW hierarchy can be applied to identify diesel wastage and theft in an open-cast mining environment. The work established DIKW as an effective diagnostic solution to assist mining companies with decision-making.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation